Contemporary Islamic Economic Law: Autonomous Smart Contracts and the Legal Dilemma of Liability for Technical Errors - Sabir M. Al-Mezel; Samir M. Al-Dalalah; Nabeel F. Al-Shatnawi; Mohammad Fawwaz Matalkaha; Abd Alhade Mossa Hasan Rshdan (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
Contemporary Islamic economic law faces emerging challenges arising from the rapid development of autonomous smart contracts and blockchain-based automated contracting systems. This study examines the legal and Islamic jurisprudential implications of autonomous smart contracts and the allocation of liability for technical errors in digitally executed agreements. It aims to analyze the validity of automated contracting under contemporary Islamic economic law and comparative legal frameworks, particularly in relation to blockchain-based systems and electronic agents. Using a doctrinal legal research methodology, the study applies descriptive, analytical, and comparative approaches, drawing on statutory provisions, international conventions, and principles of Islamic jurisprudence, including liability (ḍamān), causation (sababiyyah), and risk-bearing (al-ghurm bi al-ghunm). The findings indicate that autonomous smart contracts are generally valid under both positive law and Sharia when they reflect prior human consent encoded in automated systems and comply with the requirements of clarity, legality, and the absence of excessive uncertainty. However, significant legal uncertainty persists regarding liability for technical errors, system malfunctions, and programming defects occurring during automated execution. The study concludes that responsibility is primarily attributed to the owner or operator of the automated system, as supported by comparative legal doctrines treating electronic agents as instruments of the contracting party and by Islamic principles linking profit with liability. Accordingly, the research contributes to bridging classical Islamic legal theory and modern digital contracting environments while highlighting the need for clearer regulatory frameworks to address emerging technological risks.